Enhancing cellular immunogenicity of MVA-vectored vaccines by utilizing the F11L endogenous promoter. Issue 1 (2nd January 2016) - Alharbi, Naif Khalaf; Spencer, Alexandra J.; Salman, Ahmed M.; Tully, Claire M.; Chinnakannan, Senthil k.; Lambe, Teresa; Yamaguchi, Yuko; Morris, Susan J.; Orubu, Toritse; Draper, Simon J.; Hill, Adrian V.S.; Gilbert, Sarah C.
Highlights: This study presents the effect of stronger promoters on MVA immunogenicity. F11 promoter (pF11) enhanced in vivo transgene expression and immunogenicity. pF11 proved stronger than mH5 and p7.5 promoters. pF11 was tested with a reporter transgene as well as candidate vaccine antigens. Mechanisms underlying the improved immunogenicity with pF11 were investigated. Abstract: Modified vaccinia virus Ankara (MVA)-vectored vaccines against malaria, influenza, tuberculosis and recently Ebola virus are in clinical development. Although this vector is safe and immunogenic in humans, efforts remain on-going to enhance immunogenicity through various approaches such as using stronger promoters to boost transgene expression. We previously reported that endogenous MVA promoters such as pB8 and pF11 increased transgene expression and immunogenicity, as compared to the conventional p7.5 promoter. Here, we show that both promoters also rivalled the mH5 promoter in enhancing MVA immunogenicity. We investigated the mechanisms behind this improved immunogenicity and show that it was a result of strong early transgene expression in vivo, rather than in vitro as would normally be assessed. Moreover, keeping the TK gene intact resulted in a modest improvement in immunogenicity. Utilizing pB8 or pF11 as ectopic promoters at the TK locus instead of their natural loci also increased transgene expression and immunogenicity. In addition to a reporter antigen, the pF11 promoter was tested with the expression of two vaccine antigens for which cellular immunogenicity was significantly increased as compared to the p7.5 promoter. Our data support the use of the pF11 and pB8 promoters for improved immunogenicity in future MVA-vectored candidate vaccines.